Application of Stable Isotopes in Aquaculture Nutrition Research - Focken, Ulfert (Facultad de Ciencias Biologicas, 2008)
The carbon and nitrogen contained in fish tissue originate from the diet of the animal. The ratio of the stable isotopes(13C/12C, 15N/14N) of the diet is transferred (with a small, but important modification) to the tissue of the fish.Therefore, the analysis of stable isotopes in fish tissues provides information on the isotopic composition of thefish’s diet. This analysis is of special interest in semi-intensive aquaculture systems, in which the growth depends onnatural food as well as on compound feed, and in which alternative methods for the study of diet composition aredifficult to apply. Other fields for application of this method are the tracing of individual components from abalanced diet in the metabolism of fish, e.g. the tracing of the metabolic fate of different protein (fish meal, plantprotein) in fish metabolism.